Leveraging Big Data Analytics for Enhanced Commercial Vehicle Safety: FMCSA's Data Engineering Journey - Janardhan Reddy Kasireddy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The Federal Motor Carrier Safety Administration (FMCSA) has transformed from a traditional regulatory body into a data-driven organization leveraging advanced analytics, real-time processing, and artificial intelligence to enhance commercial vehicle safety. This technical article examines how FMCSA implemented sophisticated data engineering solutions to process millions of annual inspections through the Motor Carrier Management Information System (MCMIS). By addressing challenges related to data volume, variety, velocity, and veracity, FMCSA established a robust foundation for safety oversight. The architectural evolution from batch to real-time processing through Change Data Capture (CDC) methodologies dramatically reduced latency in safety data propagation. Machine learning models now analyze historical inspection and crash data to predict future risks, enabling proactive enforcement. The transformation yielded substantial improvements in processing latency, system availability, data quality, and inspection efficiency, while future initiatives focus on telematics integration, anomaly detection, and federated learning approaches.
Keywords: Artificial Intelligence; Big Data; Regulatory Compliance; Safety Enforcement; Telematics